Volumetric properties of (dialkyl carbonate + n-alkane) mixtures at high pressures: Experimental measurement and Nitta–Chao model prediction - Ana Gayol (2013)
The present work reports valuable experimental high-pressure density data for dimethyl carbonate, diethyl carbonate, n-octane, n-decane pure components and their binary mixtures (dialkyl carbonate + n-alkane) at temperatures between (288.15 and 308.15) K and pressures between (0.1 and 40) MPa. The experimental density values were compared with experimental information available in the literature. While the volumetric properties for (dimethyl carbonate + n-alkane) were reported in many works, the (diethyl carbonate + n-alkane) were less studied. The purpose of this study is to extend the available experimental information about the thermophysical behavior of this kind of mixtures, which is useful in the fuel field. The experimental density data were correlated using a modified Tait equation and were predicted by Nitta–Chao group contribution model.